TRIM28 in cancer and cancer therapy - Li, Kailang; Wang, Haifeng; Jiang, Bitao; Jin, Xiaofeng (Frontiers in Genetics, 2024)
TRIM28 (tripartite motif protein 28) was initially believed to be a transcription inhibitor that plays an important role in DNA damage repair (DDR) and in maintaining cancer cellular stemness. As research has continued to deepen, several studies have found that TRIM28 not only has ubiquitin E3 ligase activity to promote degradation of substrates, but also can promote SUMOylation of substrates. Although TRIM28 is highly expressed in various cancer tissues and has oncogenic effects, there are still a few studies indicating that TRIM28 has certain anticancer effects. Additionally, TRIM28 is subject to complex upstream regulation. In this review, we have elaborated on the structure and regulation of TRIM28. At the same time, highlighting the functional role of TRIM28 in tumor development and emphasizing its impact on cancer treatment provides a new direction for future clinical antitumor treatment